Liuwei Dihuang Pills Inhibit Podocyte Injury and Alleviate IgA Nephropathy by Directly Altering Mesangial Cell-Derived Exosome Function and Secretion - Zhu, Xiaodong; Shen, Xiaogang; Lin, Bo; Fang, Jiaxi; Jin, Juan; He, Qiang (Frontiers in Pharmacology, 2022)
Background: Immunoglobulin A nephropathy (IgAN) is the most common glomerular disease worldwide. Its pathological features include IgA immune complex deposition, accompanied by mesangial cell proliferation and mesangial matrix expansion. This study was conducted to investigate the effects of Liuwei Dihuang pills (LWDHW) on IgAN in mice and human podocytes, as well as to determine their underlying mechanisms of action. Methods: For in vitro experiments, podocytes were exposed to the human mesangial cell culture medium supernatant of glomerular cells treated with aggregated IgA1 (aIgA1) and LWDHW-containing serum. Cell viability and the proportion of positive cells were evaluated using CCK-8 and flow apoptosis kits, respectively. The cells were collected for western blot analysis. Twenty-four mice with IgAN induced by oral bovine serum albumin administration combined with tail vein injection of staphylococcal enterotoxin B were randomly divided into four groups of six mice each: untreated model group, model+ LWDHW group, model+rapamycin group, and model+LWDHW+rapamycin group. The normal control group contained six mice. The red blood cell count in the urine, urine protein, blood urea nitrogen, serum creatinine, and IgA deposition were determined, and TUNEL and western blotting were performed in the mouse kidney tissues. Results: In vitro experiments showed that LWDHW promoted autophagy by regulating the PI3K/Akt/mTOR signalling pathway and improved the damage to podocytes caused by the aIgA1-treated mesangial cell supernatant. This study demonstrates the effectiveness of LWDHW for treating IgAN. In the animal experiments, LWDHW significantly reduced the urine red blood cell count, serum creatinine and urea nitrogen contents, and 24 h urinary protein function and improved IgA deposition in the kidney tissues, glomerular volume, glomerular cell proliferation and polysaccharide deposition, and glomerular cell apoptosis. The pills also reversed the changes in the LC3II/I ratio and p62 content in the kidney tissues. The combination of LWDHW and rapamycin showed stronger inhibitory effects compared to those of LWDHW or rapamycin alone. Conclusion: LWDHW may improve regulation of the PI3K-Akt-mTOR pathway and inhibit autophagy in podocytes, as well as alleviate IgA nephropathy by directly altering mesangial cell exosomes.